0D, 1D, 2D molybdenum disulfide functionalized by 2D polymeric carbon nitride for photocatalytic water splitting. (9th June 2021) - Aleksandrzak, Malgorzata; Baca, Martyna; Pacia, Michał; Wenelska, Karolina; Zielinska, Beata; Kalenczuk, Ryszard J; Mijowska, Ewa
Abstract: Photocatalytic activity of molybdenum disulfide structures with different dimensions (0D, 1D and 2D) functionalized with polymeric carbon nitride (PCN) is presented. MoS2 nanotubes (1D), nanoflakes (2D) and quantum dots (0D, QDs) were used, respectively, as co-catalysts of PCN in photocatalytic water splitting reaction to evolve hydrogen. Although, 2D-PCN showed the highest light absorption in visible range and the most enhanced photocurrent response after irradiation with light from 460 to 727 nm, QDs-PCN showed the highest photocatalytic efficiency. The detailed analysis revealed that the superior photocatalytic activity of QDs-PCN in comparison with other structures of MoS2 arose from (i) the most effective separation of photoexcited electron–hole pairs, (ii) the most enhanced up-converted photoluminescence (UCPL), (iii) the highest reactivity of electrons in conduction band. Moreover, a narrowed size of QDs affected shorter diffusion path of charge carriers to active reaction sites, higher number of the sites and higher interfacial area between molybdenum disulfide and PCN.